Comparative Study of the Pathological Effects of Western Equine Encephalomyelitis Virus in Four Strains of Culex tarsalis Coquillett (Diptera: Culicidae) - Neira, Marco V.; Mahmood, Farida; Reisen, William K.; James, Calvin B. L.; Romoser, William S. (Frontiers in Public Health, 2014)
Early reports suggested that mosquito cells infected with arboviruses remain viable and undamaged. However, more recent experimental evidence suggests that arboviral infection of mosquito tissues might indeed result in pathological changes, with potential implications for vector survival and virus transmission. Here, we compare the pathological effects of western equine encephalomyelitis virus (WEEV) infection in four strains of Culex tarsalis previously reported to differ in their competence as WEEV vectors. Pathological effects were observed in cells of the midgut epithelium, salivary glands, and eggs. Cell rounding and sloughing of midgut epithelial cells was associated with those strains reported to be the least susceptible to WEEV infection, whereas midgut necrosis and vacuolation upon infection were associated with strains showing higher susceptibility. Although pathological effects were sporadically observed in infected salivary glands, further studies are required to evaluate their impact on vector competence. Additionally, the potential implications of observed C. tarsalis egg infection with WEEV are discussed.